(3GdeMLI GdHjVGA aj EMjGA GdCMjGAs - (3GdcGTj Ch GdcGTGfj, GdeJCdg GdMcje, eMSf Hf eQJVi Hf ajV Gddg eMehO, J (B1090 (3g`s
(3ChdgG (B:s
(3cJGH BOGH GdCcd hgh GdQHY GdChd ef QHY GdYGOGJ ef GdeMLI GdHjVGA (B... (3GdMeO ddg (B..(3HEf ebUO Phj GdCdHGH dbGA Gddg SHMGfg HOGQ GdKhGH hdG WQjb ddhUhd Edi GddbGA EdG HGdYde hGdYed hdG jecf GdehGXHI YdjgeG ZdG HSdGeI GdHOf hdG JUah SdGeI GdHOf EdG HGdCWYeI (B...s
(3BNQgG (B:s
.. (3hGf djS GdeQGO HgG eMHI TNUjI GdehLhO aj GdOfjG eOI GdeMShS HGdMhGS GdLRFjI Hd GdeQG eMHI MbjbjJg GdEdgjI hebGeg GdYbdj Gdcdj (B...(3gPG BNQ GdcdGe aj cJGH GNdGb GdEeGeI hBOGH GdTjYIs
(3efbhdI Yf fSNI HNW GdeDda cJHgG (B1049 (3g`s
(3JHUQI GdeDda (B:s
(3jbhd GdRQcdj (B: (3hQO GSeg (B" (3eMSf Hf eQJVi (B" (3h (B" (3eMSf Hf eMqeO (B" (3h (B" (3eMeO eMSf (B" (3hbjd dg (B" (3GdajV (B" (3hYQa LOg HajV Gddg hHGdajV(B. (3hLGAJ fSHJg (B" (3GdcGTj (B" (3h (B" (3GdcGTGfj (B" (3h (B" (3GdbGTGfj (B" (3hjbGd dg(B: (3edG eMSf ajV GdcGTjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\290s
(3GdPQjYI (B20 - 100 (2314)s
Keywords: (3GdJUha hGdBOGH GdTQYjIs